Learning - Kingsbury, Karen (Grand Rapids, MI : Zondervan, 2011)
Bailey Flanigan and Cody Coleman are not only separated by physical distance, they are also faced with great emotional distance. Bailey grows closer to her dream to be an actress and dancer in New York, while Cody coaches a small high school football team, on and off the field. But neither feels complete without the chance to share their dreams with one other.
Sequel to: Leaving.
Includes Discussion questions (p. 333-334).
Keywords: Young women -- Fiction; Coaches (Athletics) -- Fiction; Christian fiction; Love stories